1981
DOI: 10.1111/j.1469-8749.1981.tb02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Co‐ordination in Adolescent Boys with Reading Retardation

Abstract: SUMMARY The temporal organization of unimanual and bimanual rhythmic finger‐tapping was compared between adolescent normal readers and retarded readers, as well as across subgroups of retarded readers with different psychometric intelligence profiles. Regardless of subtype, the retarded readers had substantially greater difficulty in maintaining a steady tapping rhythm than did controls, but their deficit was limited to motor tasks requiring asymmetrical timing commands to the two hands. The findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Synchronization of both hands in bilateral aiming movements appears as early as 5 to 6 years of age (Fagard et al 1985, Fa@ 1987, Hay 1990). However, c h i l h n with drjlcxia and other types of reading disorder have been reported to have difficulty in performing tasks that require precise bilateral motor coordination (Klicpera et d. 1981, Wolff et al 1984, van Dellen and G e m 1986, WoBand Drake 1991, Geuze and Kalveher 1994. These studies indicate that deficits in the coordination of the two hands are often Limited to motor tasks which involvc asymmetrical movements.…”
mentioning
confidence: 99%
“…Synchronization of both hands in bilateral aiming movements appears as early as 5 to 6 years of age (Fagard et al 1985, Fa@ 1987, Hay 1990). However, c h i l h n with drjlcxia and other types of reading disorder have been reported to have difficulty in performing tasks that require precise bilateral motor coordination (Klicpera et d. 1981, Wolff et al 1984, van Dellen and G e m 1986, WoBand Drake 1991, Geuze and Kalveher 1994. These studies indicate that deficits in the coordination of the two hands are often Limited to motor tasks which involvc asymmetrical movements.…”
mentioning
confidence: 99%
“…Further, the deficits that appear when dyslexic individuals attempt to execute simple and complex neuromotor acts, combined with the presence of clinical signs (such as dysrhythmia and synkinetic movements) [ 63 , 64 , 65 , 66 , 67 ], have historically all been considered related to the abnormal temporal organization of motor skills [ 67 , 68 ]. However, considering the additional impairments found in executive functions such as programming movements, in visual and kinaesthetic sensory processes, and in the capacity to evaluate their own performance and correct their errors, Chiarenza [ 69 ] advanced the hypothesis that dyslexia is not only a phonological deficit but “ is a more complex disorder associated with a malfunction of higher cognitive functions, including attention, phonological analysis, verbal-motor coordination, control mechanisms and feedback, and memory ” [ 70 ].…”
Section: What Is Dyslexia: Models and Neuronal Correlatesmentioning
confidence: 99%
“…Furthermore, clinical signs such as dysrhythmia, the presence of synkinetic movements, have often been described in dyslexic individuals (Adams et al1974, Kennard 1960, Rutter et al, 1966, Stine et al, 1975, Wolff and Hurvitz, 1973, Denckla 1973). These difficulties were interpreted as a disorder of the temporal organization of motor skills (Klicpera et al, 1981, Denckla 1973). These observations were also recently confirmed by Punt et al (2010), who reported that 87% of dyslexics exhibit minor neurological dysfunction, especially in fine manipulative skills, the regulation of muscle tone, and the excessive presence of associated movements.…”
Section: Figure 2 -Figure 2 Shows the Averaged Movementrelated Brain mentioning
confidence: 99%